2006
DOI: 10.1021/ol060530l
|View full text |Cite
|
Sign up to set email alerts
|

Double Lawton SN2‘Addition to Epoxyvinyl Sulfones:  Selective Construction of the Stereotetrads of Aplyronine A

Abstract: [reaction: see text] Enantiopure epoxyvinyl sulfones function as templates for the diastereoselective construction of the three stereotetrads of aplyronine A. Lawton S(N)2' addition of 3,5-dimethylpyrazole followed by its displacement in an alcohol-directed Lawton S(N)2' reaction establishes the required product stereochemistry with high selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…Fiaud et al suggested an antiperiplanar orientation of metal and the nucleophile (–NHTs group) [6]. According to the S N 2' substitution reaction mechanism [2730], nucleophiles attack the double bond from the same side from which the leaving group departs, as shown below (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Fiaud et al suggested an antiperiplanar orientation of metal and the nucleophile (–NHTs group) [6]. According to the S N 2' substitution reaction mechanism [2730], nucleophiles attack the double bond from the same side from which the leaving group departs, as shown below (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…28 They previously established the stereoselective synthesis of vinyl sulfone 56 as a starting material of the C15-C20 part ( Figure 5). 30 These vinyl sulfones 59 and 69 were used as precursors of C5-C11 and C21-C27 segments 62 and 73, respectively. 30 These vinyl sulfones 59 and 69 were used as precursors of C5-C11 and C21-C27 segments 62 and 73, respectively.…”
Section: Fuchs's Ring-opening Reaction Of Chiral Cyclic Vinyl Sulfonementioning
confidence: 99%
“…29 They also developed a stereoselective method of synthesizing seven-membered vinyl sulfones 59 and 69 involving four contiguous stereogenic centers by using the double Lawton SN2' addition as a key step. The seven-membered vinyl sulfone 69, 30 On the other hand, they synthesized the C15-C27 segment 75 by using Julia-Kocienski olefination 31 as a key step (Scheme 12).…”
Section: Fuchs's Ring-opening Reaction Of Chiral Cyclic Vinyl Sulfonementioning
confidence: 99%
See 1 more Smart Citation
“…32 can be methylated in a second regio-and stereo-specific S N 2 reaction with MeMgBr de (Scheme 12) to give >95% yield with 95% of (26) with the methyl group syn to the OH group. Surprisingly, when the temperature of the methylation was lowered to 0 • C, the syn:anti ratio decreased from 20:1 to 1:1 and it was reduced further to 1:4 at −45 • C. This temperature dependence was attributed to an equilibrium between two conformations of the magnesium alkoxide intermediates in the methylation reaction.…”
Section: Reactions Of Cyclic Ethersmentioning
confidence: 99%